Penjadwalan Waktu Preventive Maintenance untuk Meningkatkan Kinerja Mesin Frais dan Bubut di PT. Isumi - Willy Widyaswara Pradana; Wiwin Widiasih (Universitas Merdeka Malang, 2023)
PT Industri Sumber Mesin Indonesia (ISUMI) is a company engaged in manufacturing services for vehicle and engine spare parts, The company is located at Jalan Raya Mastrip Kedurus No. 44A Karang Subdistrict, Pilang, Surabaya City, in the production system using manual Frais and Lathe machines with old types. In order for the machine to function properly, routine maintenance is needed, The need for periodic checks every day also affects the performance of the machine and to reduce the occurrence of downtime that is too long so as not to affect production activities in the factory. PT Industri Sumber Mesin Indonesia (ISUMI) uses a series production system, if a problem occurs on one machine, the production process will be disrupted as a whole resulting in not achieving the company's production targets. Therefore, research is made using the Failure Mode Effect Analysis (FMEA) method to determine the Risk Priority Number Value or the total risk priority number value of all components of milling machine No.1 amounting to (601), the total of all components of lathe machine No. 2 amounting to (490). The proposal determines the maintenance interval time for milling machine component No. 1 fanbelt 68 days, spindle pin 61 days, cutter tool 74 days, dynamo 163 days, gear box 57 days. Lathe machine component No. 2 chuck 79 days, tool blade 74 days, fead shaft 110 days, tail stock 69 days. Calculation of costs before and after the proposed maintenance of milling machine No. 1, which amounted to Rp. 15,930,000 and carried out proposed maintenance of the machine with a reliability value of 50% the cost decreased to Rp. 10,824,117 the difference in costs decreased by Rp. 5,105,883, lathe No. 2, which amounted to Rp. 10,287,000 and carried out proposed maintenance of the machine with a reliability value of 50% the cost decreased to Rp. 5,737,542.11 the difference in costs decreased by Rp. 5,086,574.89.Â Keywords: Preventive maintenance, Failure Mode Effect Analysis (FMEA), Proposed machine maintenance, maintenance costs.